2021
DOI: 10.1111/jgh.15631
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumor necrosis factor‐α levels in non‐alcoholic fatty liver disease: A systematic review and a meta‐analysis

Abstract: Background and Aim To synthesize data on circulating tumor necrosis factor (TNF)‐α levels between patients with histologically confirmed non‐alcoholic fatty liver disease (NAFLD) (simple steatosis or non‐alcoholic fatty liver [NAFL] and/or non‐alcoholic steatohepatitis [NASH]) and controls. Methods We performed a systematic search in PubMed, Scopus, and Cochrane Library. Fifty‐six studies, published between 2003 and 2019, were finally included, reporting data from 5848 individuals (1634 controls and 4214 NAFLD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 82 publications
(204 reference statements)
1
28
0
1
Order By: Relevance
“…Correspondingly, recent clinical data showed that patients with NAFLD had significantly compromised cardiac and autonomic function, and, in particular, the raised levels of TNF-α and CK-18 (as markers for liver injury) in NAFLD patients were independently connected with augmented sympathetic activity and reduced parasympathetic activity [179]. Moreover, NAFLD has been reported to be related to systemic inflammatory responses, characterized by elevated levels of cytokines IL-6 and TNF-α [180,181]. Proinflammatory cytokine, such as the mentioned H. pylori-related TNF-α and IL-6, have been revealed to regulate the expression of the mentioned RAAS components, especially angiotensinogen production in the liver and kidneys, further promoting systemic and local angiotensin II formation and angiotensin II-dependent hypertension [182].…”
Section: H Pylori and Mets-related Nafld And Arterial Hypertensionmentioning
confidence: 98%
“…Correspondingly, recent clinical data showed that patients with NAFLD had significantly compromised cardiac and autonomic function, and, in particular, the raised levels of TNF-α and CK-18 (as markers for liver injury) in NAFLD patients were independently connected with augmented sympathetic activity and reduced parasympathetic activity [179]. Moreover, NAFLD has been reported to be related to systemic inflammatory responses, characterized by elevated levels of cytokines IL-6 and TNF-α [180,181]. Proinflammatory cytokine, such as the mentioned H. pylori-related TNF-α and IL-6, have been revealed to regulate the expression of the mentioned RAAS components, especially angiotensinogen production in the liver and kidneys, further promoting systemic and local angiotensin II formation and angiotensin II-dependent hypertension [182].…”
Section: H Pylori and Mets-related Nafld And Arterial Hypertensionmentioning
confidence: 98%
“…T cell [27]. In human biomarker studies, higher circulating TNFa level was 14 associated with NAFLD [28] and future NAFLD [29]. In NAFLD patients, soluble IL1R1 was higher (Ajmera et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A number of genes have been reported as NAFLD biomarkers in humans. For hepatocytes, we found Il1r1 [43], Il1r2 and Tnf [28]. For endothelial cells, there was Hgf [4446].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A key feature is the low‐grade inflammatory state, which characterizes NAFLD and extends beyond the liver 9 . In NAFLD, chronic production of proinflammatory cytokines (eg, tumour necrosis factor‐α [TNF‐α], interleukin [IL]‐1, IL‐6, IL‐17), 10 produced mainly by the inflammatory cells infiltrating hepatic and adipose tissue, and adipokines (leptin, resistin, retinol‐binding protein‐4, visfatin, chemerin), produced mainly by the adipocytes, create a milieu of a chronic systemic inflammatory process, known as “metabolic inflammation” 11,12 . This inflammatory cascade promotes the progression of NAFLD in the liver and links NAFLD to extrahepatic chronic diseases, possibly including osteoporosis.…”
Section: Potential Mediators Linking Nafld With Osteoporosismentioning
confidence: 99%